Proceedings of the Second Workshop on Analytics for Noisy Unstructured Text Data 2008
DOI: 10.1145/1390749.1390755
|View full text |Cite
|
Sign up to set email alerts
|

Named entity normalization in user generated content

Abstract: Named entity recognition is important for semantically oriented retrieval tasks, such as question answering, entity retrieval, biomedical retrieval, trend detection, and event and entity tracking. In many of these tasks it is important to be able to accurately normalize the recognized entities, i.e., to map surface forms to unambiguous references to real world entities. Within the context of structured databases, this task (known as record linkage and data de-duplication) has been a topic of active research fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 22 publications
0
32
0
4
Order By: Relevance
“…Entity linking has been applied to many different specific domains. Jijkoun et al [106] studied this as an entity normalization task in blogs and comments. He et al [94] showed that applying entity linking to radiology reports did not yield satisfactory results and propose a sequential labeling approach, with syntactic features.…”
Section: Link Generationmentioning
confidence: 99%
“…Entity linking has been applied to many different specific domains. Jijkoun et al [106] studied this as an entity normalization task in blogs and comments. He et al [94] showed that applying entity linking to radiology reports did not yield satisfactory results and propose a sequential labeling approach, with syntactic features.…”
Section: Link Generationmentioning
confidence: 99%
“…It has recently gained new interest, primarily within the context of Wikipedia, looking at cross-referencing documents [20,24,28], missing link detection [11], automatic approaches for hyperlinking [12,15], automatically linking documents to encyclopaedic knowledge [16,23,26], and entity linking augmented with human intelligence [9]. Link generation approaches are also used in disambiguation tasks [6,8,18]. Many of these works are not directly comparable to ours because of different aims and a reliance on properties specific to Wikipedia.…”
Section: Related Workmentioning
confidence: 99%
“…This problem is treated as disambiguation. (d) Normalization: despite Hakenberg definition of normalization as a disambiguation procedure [10], in the present work, normalization is understood as the process of relating NEs mentioned in the texts to entries in databases structured with biological data, such as ontologies or genetic sequencing databases [11][12][13]. (e) Recognition, identification, or extraction: the terms recognition, identification, and extraction are treated as synonyms in this taxonomy.…”
Section: Applicationmentioning
confidence: 99%